Standar Isi Artikel Penelitian: Komponen Detail untuk Dipublikasikan di Jurnal Ilmiah - Muhammad Asy'ari; Muhammad Roil Bilad; Muhali Muhali (Empiricism Journal, 2022)
Peningkatan publikasi ilmiah Indonesia pada jurnal ilmiah mengalami peningkatan pesat. Pada tahun 2019-2020, Indonesia bahkan berada pada peringkat 1 di ASEAN. Sayangnya peningkatan jumlah publikasi tersebut tidak dibarengi dengan peningkatan jumlah sitasi sehingga menunjukkan minimnya kualitas tulisan ilmiah Indonesia. Permasalahan tersebut dapat disebabkan oleh kurangnya kemampuan dalam menulis karya tulis ilmiah. Artikel ini bertujuan untuk menguraikan standar isi pada tiap komponen artikel ilmiah seperti abstrak, pendahuluan, metode, hasil dan pembahasan, dan kesimpulan/implikasi. Tiap komponen tersebut setidaknya berisi 200-250 kata yang terdiri dari 18 paragraf sehingga total jumlah kata pada satu artikel ilmiah adalah 3600-4500 kata. Detail isi pada setiap paragraph dijelaskan lebihlanjut pada artikel ini. Standard Content of Research Paper: Detail Component to Get Publish in Scientific Journal Abstract The increase of Indonesian scientific publications in scientific journals has increased rapidly. In 2019-2020, Indonesia is even ranked 1st in ASEAN. Unfortunately, the increase in the number of publications was not accompanied by an increase in the number of citations, thus indicating the low quality of Indonesian scientific writings. These problems can be caused by a lack of ability in writing scientific papers. This article aimed to describe the content standards for each component of scientific articles such as abstracts, introductions, methods, results and discussion, and conclusions/implications. The components of the scientific article must contain at least 200-250 words consisting of 18 paragraphs so that the total number of words in one scientific article is 3600-4500 words. Details of the contents of each paragraph are explained further in this article.